An NIR-II-absorbing photothermal agent containing multiple rotors with enhanced photothermal conversion capacity for multimodal-imaging-guided photothermal therapy. (February 2023) - Huang, Chenchen; Shi, Tingyu; Zhang, Jinjin; Sun, Yiqi; Ma, Tiantian; Li, Wen; Li, Yang; Qiu, Huayu; Yin, Shouchun
Abstract: Second near-infrared (NIR-II) photothermal agents (PTAs) have attracted immense attention for cancer theranostics due to their weak interaction with biological tissues, deep tissue penetration, and high maximum permissible exposure, which facilitate excellent imaging-guided tumor therapy. However, the existing NIR-II organic small molecule PTAs predominantly emit in the NIR-II window, and are irradiated by visible light (660 nm) or first near-infrared light (808 nm), hindering efficient deep-tissue photothermal therapy (PTT). Here, a D2 -D1 -A-D1 -D2 structure-based photothermal agent was developed for enhanced NIR-II-absorbed trimodal-imaging-guided PTT upon 1064 nm irradiation; the developed PTA (BBTD-TP) absorbed long wavelengths (over 1000 nm) via intramolecular charge transfer through enhanced donor-acceptor conjugation. After DSPE-PEG2000 coating, the BBTD-TP nanoparticles (NPs) containing molecular rotors and long alkyl chains exhibited a high photothermal conversion efficiency (37.8%) under 1064 nm laser irradiation, which could be utilized for photoacoustic imaging (PAI) and photothermal imaging (PTI). Furthermore, the BBTD-TP NPs retained their fluorescence emission, facilitating fluorescence imaging (FLI). As a combinatorial theranostic nanoplatform, the multifunctional BBTD-TP nanomachine exhibited excellent tumor-ablation performance under 1064 nm laser irradiation, enabling efficient PAI/PTI/FLI-guided PTT in nude mice with B16F10 cells. Thus, this study reports a highly efficient NIR-II PTA and could guide the future design and development of similar PTAs for efficient theranostics. Graphical abstract: Schematic illustration of the therapeutic performance for multimodal-imaging-guided photothermal therapy. Image 1 Highlights: Second near-infrared (NIR-II) photothermal agents (PTAs) for cancer theranostics. Intramolecular charge transfer through enhanced donor-acceptor conjugation. High photothermal conversion efficiency (37.8%) under 1064 nm laser irradiation. Trimodal-imaging-guided photothermal therapy in nude mice with B16F10 cells.